Quantitative analysis of soft-bottom polychaetes of the Bellingshausen Sea and Gerlache Strait (Antarctica) - Parapar, Julio; López, Eduardo; Gambi, Maria Cristina; Núñez, Jorge; Ramos, Ana (Polar Biology, 2011)
The basin off the Bellingshausen Sea, in contrast to other better known areas such as the Antarctic Peninsula and the Ross and Weddell Seas, has been little investigated due to remoteness and the prevalence of ice for most of the year. The present study focuses on an analysis of polychaetes collected from soft bottoms of this sea and off the west coast of the Antarctic Peninsula (Gerlache Strait) by means of a box-corer (25 × 25 cm) in two intensive surveys carried out during austral summers of 2002–2003 and 2005–2006 (BENTART-03 and BENTART-06). Three different polychaete assemblages were determined from the classification and ordination analyses of sampling stations based on the Bray-Curtis similarity index. One group of stations encompassed the deep stations from the shelf of the Bellingshausen Sea, the second one the shallower stations from the same area and the third one those stations located near the coast of Peter I Island and Gerlache Strait, off the Antarctic Peninsula. The environmental variables involved in segregating these groups were several sedimentary features (redox potential, gravel content) and depth. The present study provides further support to previous ones that considered the shelf of the Bellingshausen Sea as a differentiated region within the Southern Ocean, clearly distinct to the adjacent Weddell and Scott Seas and the Antarctic Peninsula. Ministerio de Ciencia y Tecnología; REN2001-1074/ANT Ministerio de Ciencia y Tecnología; CGL2004/01856